2021
DOI: 10.1186/s10086-021-01993-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of radial variations of wood properties in naturally regenerated trees of Betula platyphylla grown in Selenge, Mongolia

Abstract: Wood properties, such as annual ring width, wood fiber length, vessel element length, basic density, air-dry density, dynamic Young’s modulus, modulus of elasticity (MOE), modulus of rupture (MOR), absorbed energy in impact bending, compressive strength parallel to grain, and shearing strength, were investigated for wood from 10 naturally regenerated trees of Betula platyphylla Sukaczev in Mandal, Selenge, Mongolia. Mixed-effects models were used to evaluate the radial variations in the wood properties. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Thus, the rate of change in the aforementioned properties from the pith toward the cambium might differ among individual trees. On the other hand, the model with a y-value at the first annual ring from the pith of the individual tree was selected in vessel frequency, vessel diameter, wood Erdene-ochir et al [15] fiber diameter, wood fiber wall thickness, air-dry density, MOR, and compressive strength. This finding indicated that these wood properties depend on the values at the first annual ring, which differed among individual trees, and that the radial variation pattern itself is not affected by differences among individual trees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the rate of change in the aforementioned properties from the pith toward the cambium might differ among individual trees. On the other hand, the model with a y-value at the first annual ring from the pith of the individual tree was selected in vessel frequency, vessel diameter, wood Erdene-ochir et al [15] fiber diameter, wood fiber wall thickness, air-dry density, MOR, and compressive strength. This finding indicated that these wood properties depend on the values at the first annual ring, which differed among individual trees, and that the radial variation pattern itself is not affected by differences among individual trees.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between radial growth increments and the xylem maturation process based on radial variation patterns of single or several wood properties has been reported for several fast-growing tree species in dry [9], tropical [14], and subarctic climates [15] (Table 6). In these studies, wood properties became stable below the age of 10 years at the time of peak CAI and MAI values in L. tulipifera in Japan (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the abovementioned wood properties that are desirable for high-quality uses, other characteristics such as wood density are a major physical criterion for wood quality [6] since they are related to many other aspects of quality such as wood strength and shrinkage, fiber properties, and flexibility or stiffness, among others [7,8]. Furthermore, it has been demonstrated that wood density affects carbon storage [9][10][11].…”
Section: Introductionmentioning
confidence: 99%